2022
DOI: 10.3390/healthcare10101905
|View full text |Cite
|
Sign up to set email alerts
|

Gait Characteristics of Dynapenia, Sarcopenia, and Presarcopenia in Community-Dwelling Japanese Older Women: A Cross-Sectional Study

Abstract: Age-related decline in skeletal muscle mass and function are risk factors for reduced walking ability. This study aimed to understand the characteristic gait parameters of presarcopenia (low muscle mass only), dynapenia (low muscle function only), and sarcopenia (low muscle mass and function), which have differing skeletal muscle characteristics. Skeletal muscle mass, grip strength, and gait parameters (walking speed, cadence, step length, step width, gait angle, foot angle, stance time, swing time, and double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…As the walking speed of older adults with sarcopenia slowed significantly, the walking time increased accordingly, further compromising walking efficiency. The results of this study were also supported by the study of Mori et al [ 32 ], who evaluated the skeletal muscle mass and gait parameters of 307 older adults and found that the duration of the support period and the double support period increased and the duration of the swing period decreased in people with sarcopenia during walking. This pattern of change is consistent with the results of this study, suggesting that people with sarcopenia tend to adopt a more stable posture to compensate for unstable gait and maintain gait stability.…”
Section: Discussionsupporting
confidence: 87%
“…As the walking speed of older adults with sarcopenia slowed significantly, the walking time increased accordingly, further compromising walking efficiency. The results of this study were also supported by the study of Mori et al [ 32 ], who evaluated the skeletal muscle mass and gait parameters of 307 older adults and found that the duration of the support period and the double support period increased and the duration of the swing period decreased in people with sarcopenia during walking. This pattern of change is consistent with the results of this study, suggesting that people with sarcopenia tend to adopt a more stable posture to compensate for unstable gait and maintain gait stability.…”
Section: Discussionsupporting
confidence: 87%
“…Patients with sarcopenia exhibit gait changes due to the progressive decline in skeletal muscle mass, strength, and function. These changes are characterized by decreased single support time and increased double support time, primarily resulting from reduced muscle strength and impaired balance 34 , 35 . However, in our study, the smart insole was unable to fully capture these distinctive gait characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reveal specific quantitative gait changes associated with sarcopenia. Compared to healthy controls, sarcopenic individuals exhibit reduced step length, shortened stride length, slower walking velocity, shortened single limb support phase, and prolonged double support phase [ 25 , 26 , 27 ]. While cadence is often preserved, sarcopenic gait shows a shortened gait line, indicating reduced muscle mass [ 25 ].…”
Section: Physical Performance Test For Sarcopeniamentioning
confidence: 99%
“…While cadence is often preserved, sarcopenic gait shows a shortened gait line, indicating reduced muscle mass [ 25 ]. Sarcopenic women had a significantly slower pace and shorter steps versus normal controls in one study [ 27 ].…”
Section: Physical Performance Test For Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation